PENEGAKAN HUKUM OLEH POLISI DALAM TINDAK PIDANA KEKERASAN OLEH ANAK YANG BERBASIS KEADILAN DI KABUPATEN SIAK INDRAPURA - Hari Budiyanto (Universitas Nasional, 2018)
The inappropriate handling of juvenile delinquency and the hesitancy of law enforcement officers in dealing with crimes committed by children, directly or indirectly, have led to social aberrations. Police officers seem to lose the concept of dealing with violent crimes committed by children. Therefore, Police as guardian, protector, and public servant as well as law enforcement officers are required to quickly respond in response to the negative image.The problem studied in this research is law enforcement by police in violation of child abuse and how implication to the realization of justice in Siak Indrapura Regency, obstacle factor in law enforcement by police in violent crime by child so that the realization of justice has not been reached in Siak Indrapura Regency and the construction of law enforcement by the police against violent acts by children so that the realization of justice can be achieved in Siak Indrapura Regency.The method used in this research is with socio-legal research approach that comes from collecting data obtained from primary data and secondary data, then analyzed by qualitative analysis method.The results of this study ultimately provide an answer that law enforcement by the police in the crime of child abuse and how the implication of the realization of justice in Siak Indrapura Regency is still using violence to get the acknowledgment or information from the child offender of the crime in the investigation. The forms of violence committed by investigators are physical, psychological, or legal. Inhibiting factors in law enforcement by the police in violent acts by children so that the realization of justice has not been achieved in Siak Indrapura Regency due to lack of funding to support the implementation or activities that support the development of Decent City Children (KLA) in Siak Indrapura Regency, besides the slow recording of cases of violence which occurs in children due to the lack of manpower (Human Resources). In addition, the construction of law enforcement by the police against violent crime by children is to build or create a professional police that must be started at the stage of selection and education, so that the police have high standards of ethics and expertise, so that it can be achieved law enforcement in the enforcement of the enforcement law against child perpetrators of violent crime.Suggestion from this research is polisian of Regency of Siak Indrapura should have special unit that really focus and routinely doing counseling and socialization to society related to violent crime committed by child.Keywords: Law Enforcement, Police, Crime, Violence, Children and Justice.